The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1016/j.esxm.2020.06.007
|View full text |Cite
|
Sign up to set email alerts
|

European Society for Sexual Medicine Consensus Statement on the Use of the Cavernous Nerve Injury Rodent Model to Study Postradical Prostatectomy Erectile Dysfunction

Abstract: Introduction Rodent animal models are currently the most used in vivo model in translational studies looking into the pathophysiology of erectile dysfunction after nerve-sparing radical prostatectomy. Aim This European Society for Sexual Medicine (ESSM) statement aims to guide scientists toward utilization of the rodent model in an appropriate, timely, and proficient fashion. Methods MEDLINE and EMBASE databases were searched for basic scienc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 105 publications
2
10
0
Order By: Relevance
“…nerve damage and erectile tissue injury, which was also recommended by the consensus statement. 32 By the above methods, we identified that erectile function was significantly impaired in the BCNI group, which is similar to previous reports. 33 Furthermore, cavernosal denervation can dampen erectile function through mechanisms like increased collagen content, fibrosis, apoptosis, penile endothelial dysfunction, and oxidative stress injury.…”
Section: Radical Prostatectomy (Rp) Is One Of the Most Used Treatmentssupporting
confidence: 90%
See 2 more Smart Citations
“…nerve damage and erectile tissue injury, which was also recommended by the consensus statement. 32 By the above methods, we identified that erectile function was significantly impaired in the BCNI group, which is similar to previous reports. 33 Furthermore, cavernosal denervation can dampen erectile function through mechanisms like increased collagen content, fibrosis, apoptosis, penile endothelial dysfunction, and oxidative stress injury.…”
Section: Radical Prostatectomy (Rp) Is One Of the Most Used Treatmentssupporting
confidence: 90%
“…Also, to ensure the homogeneity of the study, we used the same microsurgical clamp for all rats' cavernous nerves to maintain consistent clamping force. Moreover, we stimulated the CN between the MPG and the nerve injury site during evaluating the erectile dysfunction to analyze both nerve damage and erectile tissue injury, which was also recommended by the consensus statement 32 . By the above methods, we identified that erectile function was significantly impaired in the BCNI group, which is similar to previous reports 33 .…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Also, the safety issue including adverse effects by selective HDAC inhibitors needs to be addressed by well‐designed clinical studies in future, because animal models might not reflect the human situation. Second, the clinical benefit of penile rehabilitation using a variety of therapeutic strategies for preventing permanent post‐RP ED has not been confirmed in most of the well‐designed clinical trials, despite the promising results by the therapeutic strategies in animal models of CN injury 8‐12,21 . This indicates that animal models might not reflect the human situation.…”
Section: Discussionmentioning
confidence: 99%
“…Fifty‐six 12‐week‐old rats, weighing 330‐360 g, were randomized into the four groups (fourteen rats per each group): sham surgery treated with saline vehicle [Group S], bilateral CNCI treated with saline vehicle [Group I], CNCI treated with SAHA (vorinostat; Selleckchem, Houston, USA), a pan‐HDAC inhibitor [Group V], and CNCI treated with an udenafil (Dong‐A, Seoul, Korea), a PDE5 inhibitor [Group P]. The sham surgery and CNCI were performed by an experienced surgeon who was blinded to group allocation, according to a recent European Society for Sexual Medicine Consensus Statement 14,21 . Briefly, after the rats were anesthetized using 10 mg/kg zoletil (Vibac Laboratories, Carros, France), the lower abdominal midline incision was performed, and the bilateral major pelvic ganglia (MPGs) were identified.…”
Section: Methodsmentioning
confidence: 99%